Jamur Rizosfer Sebagai Agen Antagonis Pengendali Penyakit Lapuk Fusarium Pada Batang Tanaman Karet (Hevea brasiliensis MuellArg) - Riza Linda, Wiwin Kamila Putri Siti Khotimah, (Jurnal Protobiont, 2015)
The stem rot disease caused by the Fusarium sp. fungus is one of the diseases found on the rubber tree (Hevea brasiliensis). This plant disease can be controlled by using a biological agent namely the rhizosphere fungus which is antagonistic to pathogenic fungi. This research aimed to find out the types of fungi from the rhizosphere of rubber tree and to find out the ability of those fungi to inhibit the growth of Fusarium sp. The Fusarium sp. fungus was isolated using the direct planting method, the rhizosphere fungus was isolated using the dilution method, the antagonistic test was conducted using the paired method. The rhizosphere fungi successfully isolated were Trichoderma sp. W1, Penicillium sp.1 W2, Penicillium sp.2 W3, Chaetomium sp. W4. The research findings showed that there was inhibition of the growth of Fusarium sp. by Trichoderma sp. with the highest antagonistic percentage by 51.08%.